Ultrafast dynamics of correlation bands following XUV molecular photoionization - Hervé, Marius; Despré, Victor; Castellanos Nash, P.; Loriot, V.; Boyer, Alexie; Scognamiglio, A.; Karras, G.; Brédy, R.; Constant, E.; Tielens, A. G. G. M.; Kuleff, Alexander I.; Lépine, F. (Nature physics, 2021)
Modern ultrashort X-ray/XUV (extreme ultraviolet) sources provide unique opportunities to investigate the primary reactions of matter upon energetic excitation. Understanding these processes in molecules on ultrafast timescales is required to improve bespoke high-energy radiation detectors, nanomedicine schemes or to study the molecular composition of interstellar media. However, current experiments struggle to provide a general framework because of the uniqueness and complexity of each system. Here we show the universal role of correlation bands—features created by electron correlation. This is done by studying ultrafast energy relaxation of size-scalable two-dimensional molecules following ionization by an ultrashort XUV pulse. We observed long lifetimes that nonlinearly increase with the number of valence electrons. A general law based on solid-like electron-phonon scattering is proposed, which explains both our results and previously reported measurements. This offers new opportunities in attosecond science and high-energy photophysics.
Published online: 16 November 2020
Gesehen am 29.06.2021